USABILITY ANALYSIS OF THE WEBSITE OF THE SOUTH SUMATERA PROVINCIAL LIBRARY SERVICE USING THE WEBUSE METHOD - Tri Oktarina; Ana Orija (Informatika, Universitas Jenderal Soedirman, 2022)
The South Sumatra Provincial Library Service is an institution that assists the Governor in organizing Government in the field of Education and uses the website to convey information to the public. The importance of usability is to measure the level of quality of the system with the intention of being easy to learn and then easy to use, encouraging users to use the system to achieve the goals of the user. Each website has a different usability level, the higher the usability value, the easier the website is for users to understand. This study aims to determine or measure the Website of the South Sumatra Provincial Library Service using the WEBUSE method. In this study, researchers used the WEBUSE method, there are 4 categories of usability (1 Content, organization and readability. (2)Navigation and links. (3)User interface design. (4)Performance and effectiveness. Data analysis using validity test, reliability using SPSS version.25. The results of the calculation of the WEBUSE method were processed with Ms.Excel 2007. The results of the overall study of the South Sumatra Provincial Library Service showed that the highest score or value was obtained by the Content, organization and readability variable with usability points of 0.80 usability level Excellent while the lowest score was in the Performance and category. usability effectivity point is 0.78 with Good usability level for the website usability level is at Good level.